'It's like a bag of pick and mix – you don't know what you are going to get': young people's experience of neurofibromatosis Type 1. (21st November 2013) - Barke, Jenny; Harcourt, Diana; Coad, Jane
Abstract Aims To explore the day‐to‐day experience of young people living with neurofibromatosis type 1 in the UK, focusing on the role that appearance plays in this experience. Background neurofibromatosis type 1 is a genetic condition, which is highly variable and unpredictable. It can result in varying degrees of visible difference (disfigurement). Both the effect of NF1 on appearance and its uncertainty can prove particularly difficult for those affected. However, very little research to date has investigated the psychosocial impact of neurofibromatosis type 1 on young people or their experiences of managing it. Design Exploratory qualitative interview study. Methods Nine young people aged 14–24, with a confirmed diagnosis of neurofibromatosis type 1, took part in semi‐structured interviews between March–September 2011. Interview transcripts were thematically analysed. Findings Three key themes were identified from the data: (1) 'Different things to different people' reflecting the variability in the condition; (2) 'Relationships and reactions' relating to individuals' social experience; and (3) 'Understanding and misunderstanding' reflecting participants' experiences with organizations and social structures. Conclusions Findings suggest a need for further research to explore young people's adaptation and management of neurofibromatosis type 1. In particular, raising awareness and understanding of the condition among professionals and in the general public was an important issue for young people. In addition, access to trustworthy information about neurofibromatosis type 1 and practical advice to support adjustment to an altered appearance and managing stigma experiences are highlighted as areas to be considered further.